Space, Place, and Children's Reading Development Mapping the Connections - Mackey, Margaret (Bloomsbury Perspectives on Children's Literature, 2022)
This open access book is a unique study of the impact of lived experience on literate life, exploring how children's reading development is affected by their home setting, and how this sense of place influences textual interpretation of the books they read. Based on qualitative research and structured around interviews with twelve participants, Space, Place and Children's Reading Development focuses on the digital maps and artistic renderings these readers were asked to create of a place (real or imagined) that they felt reflected their literate youth, and the discussions that followed about these maps and their evolution as readers. Analysing the participant's responses, Margaret Mackey looks at the rich insights offered about the impact on childhood stability after experiences such as migration; the "reading spaces" children make based on their social relationships and domestic spheres; the creation of "textual spaces" and the significance of the recurring motif of forests in the participants' maps; the importance of the Harry Potter novels; the basis of life-long reading habits; psychological spaces and whether readers visualize when they read. Blending theoretical perspectives on reading from many disciplines with the personal experiences of readers of diverse nationalities, languages, disciplinary interests, and life experiences, this is an enlightening account of the behaviors of readers, reading histories, and place-based reader responses to literature. By building greater understanding about the broad and subtle processes that enable people to read, this study refines the kind of questions we ask about reading and moves towards developing a multidisciplinary language for the study and discussion of reading practices in contemporary times. The eBook editions of this book are available open access under a CC BY-NC-ND 4.0 license on bloomsburycollections.com. Open access was funded by the Social Sciences and Humanities Research Council of Canada.